Tissue eosinophilia: a histopathological marker associated with stromal invasion but not histopathological grade in cutaneous squamous neoplasia - Duman, Nilay; Sen Korkmaz, Nilay; Erol, Zafer (The European Research Journal, 2015)
Objectives. The literature does not include any comparative study on the eosinophil count in premalignant and malignant cutaneous squamous neoplasias. Our aim was to compare the tissue eosinophilic count in actinic keratosis (AK) and cutaneous squamous cell carcinoma (SCC). Methods. The study included 20 AK and 20 invasive SCC patients. Age, gender, and lesion location were retrospectively evaluated as clinical parameters. Histopathological parameters included density of inflammation score, lesion grade, and the lesion-associated eosinophil count per 10 high-power (40×) microscopic fields, all of which were compared between groups. Results. In all, 65% of the AK group had lesions with moderate inflammation, whereas 85% of the SCC group had lesions with dense inflammation (p=0.001). The mean eosinophil count in the SCC group was significantly higher than that in the AK group, independent of the density of inflammation (p=0.000). In addition, lesion grade was not associated with the eosinophil count in either group (AK group: p=0.601; SCC group: p=0.416). Conclusions. Cutaneous SCC lesions had higher eosinophil counts than AK lesions, indicating the role of the eosinophil count as a histopathological marker of stromal invasion.